ANALISIS HUKUM YURISDIKSI MAHKAMAH PIDANA INTERNASIONAL DALAM PENYELESAIAN KASUS KEJAHATAN GENOSIDA DI MYANMAR MENURUT STATUTA ROMA - Adawiyah, Arraudatul; Deliana, Evi; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Jurisdiction is the authority possessed by the court in acting based on applicable provisionsregarding duties, functions, and objectives. The International Criminal Court has four types ofjurisdiction, namely: personal jurisdiction, criminal jurisdiction, Temporal jurisdiction, Territorialjurisdiction. as stated in the Rome Statute. Crime of genocide is one of the crimes contained in criminaljurisdiction and after this study that the events and problems that occur or experienced by RohingyaMuslims in Myanmar are crimes of genocide the elements of crime of genocide have been fulfilled. Themechanism in the Rome statute that can be taken to resolve cases of genocide crimes in Myanmar is thatthe jurisdiction of the International Criminal Court is applied at the initiative of the UN Security Councilagainst non-Parties to the Rome Statute 1998, based on Article 13 (b) of the Rome Statute 1998, keepingin mind the specified assignment in Part VII (Chapter VII) of the Charter of the United Nations (UNCharter) as the guardian of security and peace in personal, temporal and criminal jurisdiction held bythe international criminal court.The writing of this thesis uses normative legal research methods with library research, namelyby examining library materials or secondary data in the form of primary legal materials, namely relatedregulations, secondary legal materials, namely related documents and tertiary law. which is anindication of primary and secondary legal material. Secondary data that has been compiled is thenanalyzed using qualitative methods to obtain conclusions. From the results of research on the problem ofthe Jurisdiction of the International Criminal Court in solving cases of genocide crimes in Myanmaraccording to the Rome Statute.Which is an obstacle to the international criminal court in solvinggenocide crimes that occur in Myanmar, because there is one jurisdiction Court that is not fulfilled isterritorial jurisdiction. The Myanmar state is not a member of the Rome statute, does not ratify the Romestatute, nor does it make a declaration on the Rome statute. This is the reason for the lack of certaintyand legal justice obtained by Rohingya Muslims in Myanmar.Keywords: Jurisdiction, International Criminal Court, Genocide, Myanmar.